Development and Characterization of a Biocompatible CS-PVA Hydrogel Incorporated into Carica papaya Extract for Biomedical Applications - M. B, Balaji; Ridhwaan, Mohammed; Aksharaa, Anu; S, Vimal (Asian Pacific Journal of Cancer Biology, 2026)
Background: The objective of this study was to fabricate and evaluate a Carica papaya extract loadedchitosan/polyvinyl alcohol (Cp-CS-PVA) hydrogel and to assess its structural characteristics, release behavior and multifunctional biological activities for potential biomedical and wound-healing applications. Methods: Cp-CS-PVA hydrogel was prepared using a polymer blending and encapsulation approach. Surface morphology was analyzed using scanning electron microscopy (SEM). In vitro release behavior was evaluated to determine drug diffusion kinetics. Biological activities were assessed through DPPH radical-scavenging assay for antioxidant activity, α amylase inhibition for antidiabetic potential and protein denaturation assay for anti-inflammatory activity, with standard compounds used for comparison. Results: SEM analysis revealed a rough and porous surface morphology, confirming successful encapsulation of Carica papaya extract within the chitosan - PVA hydrogel. The hydrogel exhibited concentration-dependent cytotoxicity against SiHa cells with an IC₅₀ value of 24 μg/mL. The formulation showed sustained drug release over 24 hr indicating effective controlled release behavior. The hydrogel also demonstrated strong antioxidant activity, reaching 61.24% radical scavenging at 75 μg/mL, along with moderate antidiabetic and anti-inflammatory potential. Conclusion: The Cp-CS-PVA hydrogel demonstrates favorable physicochemical properties, sustained release behavior and multifunctional bioactivity, highlighting its promise as a bioactive wound-healing material and a potential therapeutic delivery platform. Further mechanistic and in vivo studies are warranted.